Urgensi Sikap Kritis Pendidik terhadap Media: Perspektif Filsafat Pendidikan Islam - Misbakhus Surur; Abdul Haris (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
As a good moral educator, one must understand the function of educational philosophy as a branch of philosophy. People who are inherently religious must be accompanied by a critical nature so as not to have old, stagnant and apologetic thoughts. Educators are always consumers of good and bad behavior in the learning process. The role of educators in media criticism is very important. Whereas Islamic education needs to be reviewed and criticized by the media. Due to the (bad) influence of the media can quickly enter our lives into our subconscious and work as the media wants. Unregulated media can be the mouthpiece of capitalism or of capitalism itself.